Indians at Work: An Informal History of Native Labour in British Columbia, 1848-1930 - Knight, Rolf (New Star Books, 1996)
[P]rovides an historical background to native labour in BC from the Gold Rush to the beginning of the Great Depression. It counters the common misconception that native people responded to European settlement and industrial development by retreating to a reserve existence. Evidence amassed from logging, transport, construction, longshoring, commercial fishing and canning, and a host of other industries shows that native Indians played a significant role in British Columbia's economy from the moment the first European explorers appeared off the coast. –Publisher's description. A massively documented history of Native Indian wage labour in British Columbia from initial European settlement in the mid 19th century to the beginning of the great depression. The first and as yet only historical study of Native Indian workers in Canada, it challenges many of the romantic misconceptions which have developed over the years. An expanded version of a title originally published in 1978. –Author's description
https://archive.org/details/indiansatworkinf0000knig/mode/2up
Keywords: British Columbia. Indians of North America; British Columbia. Labor supply; Employment; Employment. Labor supply; Indians of North America